Andrographis paniculata (Burm. f.) wall. ex nees: An updated review of phytochemistry, antimicrobial pharmacology, and clinical safety and efficacy - Hossain, Sanower; Urbi, Zannat; Hidayah, Karuniawati; Ramisa, Mohiuddin; Qrimida, Ahmed Moh; Mohamed Masaud Allzrag, Akrm; Ming, Long Chiau; Pagano, Ester; Capasso, Raffaele (MDPI AG, 2021)
Infectious disease (ID) is one of the top-most serious threats to human health globally, further aggravated by antimicrobial resistance and lack of novel immunization options. Andrographis paniculata (Burm. f.) Wall. ex Nees and its metabolites have been long used to treat IDs. Andrographolide, derived from A. paniculata, can inhibit invasive microbes virulence factors and regulate the host immunity. Controlled clinical trials revealed that A. paniculata treatment is safe and efficacious for acute respiratory tract infections like common cold and sinusitis. Hence, A. paniculata, mainly andrographolide, could be considered as an excellent candidate for antimicrobial drug development. Considering the importance, medicinal values, and significant role as antimicrobial agents, this study critically evaluated the antimicrobial therapeutic potency of A. paniculata and its metabolites, focusing on the mechanism of action in inhibiting invasive microbes and biofilm formation. A critical evaluation of the secondary metabolites with the aim of identifying pure compounds that possess antimicrobial functions has further added significant values to this study. Notwithstanding that A. paniculata is a promising source of antimicrobial agents and safe treatment for IDs, further empirical research is warranted.